Male Infertility: Evaluation and Treatment - Hamad Mohamed, ZB; Hamad Alfarisi, HA; Abdul Wahab , AY; Abd Fuaat, A; Che Mohamad, CA; Ibrahim, M (IIUM Medical Journal Malaysia, 2020)
Globally, 48.5 million couples are suffering from infertility. One of six couples in United Kingdom is categorized as infertile. In developing countries, infertility affects one of four couples. Male infertility constitutes about 40-50% of the incidence. A minimum of 30 million men worldwide are infertile. Mortality rate is higher in men with impaired semen quality than those who have normal semen quality. The initial evaluation of a male partner of an infertile couple should be done if there is a delay in the pregnancy in the female partner for one year or more from unprotected sexual intercourse. It can be done earlier if there is a predisposing factor for infertility. Identification of the underlying aetiology of infertility is the guide for treatment course which could be medical, surgical or through assisted reproductive technology. The aim of this review is to highligh the main courses of evaluation and treatment of male infertility.